Analisis Penerapan Projek Penguatan Profil Pelajar Pancasila dalam Pembentukan Karakter Siswa Sekolah Dasar - Ramallah, Ryaz; Fidrayani, Fidrayani (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research aims to explain and compare research results from several sources regarding the application of P5 to shape the attitudes of elementary school students. The method chosen was a literature review. The research used as a reference is an article published in the period 2015-2024.  What is discussed in the research relates to the title, abstract, introduction, methods, results, discussion and conclusions. Based on the literature review, the results showed that the implementation of the P5 project in elementary schools so far has been carried out optimally in its implementation through methods and approaches that can be applied, including prioritizing differentiation in teaching and learning activities and making adjustments to small things, especially in Elementary school level. Character cultivation and P5 projects are things that cannot be separated, therefore full collaboration and awareness are really needed so that the nation's hopes can be realized in accordance with Indonesian values ​​and ideology.